Evaluation of postharvest properties in different passion fruit species during ripening - Gomes, Francielly Rodrigues; Barbosa, Moab Acacio; Rodrigues, Claudia Dayane Marques; Salazar, Alejandro Hurtado; Silveira-Neto, Americo Nunes da; Assunção, Hildeu Ferreira da; Silva, Danielle Fabíola Pereira da (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
During ripening, many transformations occur in passion fruits. The ripening stage affects fruit quality and post-harvest properties. Fruits with 65% yellow epidermis present chemical characteristics that meet industrial standards, facilitating harvest estimations and loss avoidance. Thus, this study aimed to evaluate the post-harvest properties of passion fruit species (genotypes of the yellow passion fruit and sweet passion fruit, and yellow passion fruit cultivar FB 200) during ripening. The fruits were evaluated by the color of the epidermis and the chemical characteristics of the pulp (titratable acidity, vitamin C, carotenoids, soluble solids content, and ratio). This experiment was conducted with a completely randomized design and a split-plot arrangement, where the plots were the species and the subplots were the evaluation periods (50, 58, 66, 74 and 82 days after anthesis), with four replications and 10 fruits per plot. The yellow passion fruit genotype and cultivar, harvested at 82 days after anthesis, presented desirable characteristics for the juice industry and for fresh consumption. The sweet passion fruit had a higher soluble solids content and titratable acidity ratio because of its high content of soluble solids and low acidity, which translate to a better fruit flavor.